Effects of pre-competition altitude training on the physical function of altitudetrained athletes - Qi, J.; Ma, F.; Fan, R. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Pre-competition altitude training has become an important method of improving sports performance among athletes living at sea-level. However, athletes living at altitude and training under hypoxic conditions for a long time have had some adaptive physical and biochemical metabolism changes. Therefore, it may be necessary to modify altitude training for those athletes so that its effects will benefit performance. This paper analyzed the physical function of race-walking athletes living at altitude during 33 days before competition. The results provided a reference basis for the altitude training of athletes who live at altitude. Methods a. Subjects: Walking athletes of the Qinghai province (4 male, 3 female); b. Measurements: Blood index (RBC, Hb, Hct, MCV), blood urea nitrogen (BUN), serum creatine kinase(CK), serum testosterone (T), serum cortisol (C), urine index; c. Test frequency: Blood indices were examined once per week. BUN, CK and the urine index were measured after high intensity training and during the recovery period the following morning. T and C were measured at the beginning, middle and late in the period of altitude training. Results 1) RBC and Hb of both genders decreased from the beginning of the training to the end of the 3rd week (P<0.05), and then increased later in training, but was still lower than the initial value. 2) CK and BUN did not change significantly during the experiment and the values were both in the normal range. 3) T/C ratio decreased initially and then increased. The mean value in the male athletes changed from 36.8×10-3 to 47.5×10-3, with a increment of 38.1%, while that of the female athletes changed from 2.54×10-3 to 3.96×10-3, with an increment of 55.9%. 4) Abnormal rates of the urine biochemical indices ranked from high to low were PRO (54%), NIT (18%), BLD (10%), and URO (6%). Among them BLD only appeared in one athlete, whose urine protein also showed positive reaction (+1) after training, and it didn`t disappear after adjustment in the late stage of training. Conclusions Routine blood indices such as RBC and Hb decreased in the pre-competition altitude training, which may be caused by relative high load volume and intensity. Hormone levels (T/C) increased, showing that biosynthesis of protein was enhanced and was beneficial to improving exercise performance and recovery from fatigue. The highest abnormal rate among the urine biochemical indices was PRO. BLD accompanied by positive urine protein (+1) only appeared in one athlete, which was correlated to the high training intensity. It suggested that the training load arrangement must be treated differently according to the level of athlete. The pre-competition altitude training used in athletes living at altitude should be different from that of athletes living at sea-level, and training protocolst should emphasize high intensity training to improve specific exercise ability.